2018
DOI: 10.1016/j.bbrc.2017.11.183
|View full text |Cite|
|
Sign up to set email alerts
|

Hypothesis: Hypoxia induces de novo synthesis of NeuGc gangliosides in humans through CMAH domain substitute

Abstract: Immunotherapy is a growing field in cancer research. A privileged tumor-associated antigen that has received much attention is N-glycolyl (NeuGc) GM3. This ganglioside is present in several types of cancer, but is almost undetectable in human healthy tissues. However, its non-hydroxylated variant, NeuAc GM3, is abundant in all mammals. Due to a deletion in the human gene encoding the key enzyme for synthesis of NeuGc, humans, in contrast to other mammals, cannot synthesize NeuGc GM3. Therefore the presence of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…In contrast, Neu5Gc-sialoconjugates are often highly expressed in human tumors 6–8 , a phenomenon that has been attributed to the altered metabolic properties of cancer cells with enhanced uptake and incorporation of nonhuman Neu5Gc from Neu5Gc-containing foods, such as red meat 911 . To which extent proposed CMAH-independent, alternate biosynthetic pathways also contribute to Neu5Gc expression in cancer cells in patients 1214 , remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Neu5Gc-sialoconjugates are often highly expressed in human tumors 6–8 , a phenomenon that has been attributed to the altered metabolic properties of cancer cells with enhanced uptake and incorporation of nonhuman Neu5Gc from Neu5Gc-containing foods, such as red meat 911 . To which extent proposed CMAH-independent, alternate biosynthetic pathways also contribute to Neu5Gc expression in cancer cells in patients 1214 , remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…NeuGc GM3 is structurally highly similar to the ganglioside N -acetyl GM3 (NeuAc GM3), with the only difference being an additional oxygen atom found in NeuGc GM3. The presence of NeuGc GM3 in certain human cancer types remains enigmatic 18 20 . NeuAc GM3 can be converted to NeuGc GM3 by cytidine monophosphate- N -acetylneuraminic acid hydroxylase (cmah) 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, the expression of NeuGc-containing gangliosides has been shown to be triggered by hypoxic conditions [17]. In particular, Bousquet et al confirmed the capacity of hypoxia to induce NeuGcGM3 in HeLa cells [18].…”
Section: Discussionmentioning
confidence: 99%